Activities of the wintering party of the 23rd Japanese Antarctic Research Expedition in 1982-1983 - Takao Hoshiai (National Institute of Polar Research, 1984)
The wintering party of the Japanese Antarctic Research Expedition (1982-1983) consisting of 34 members carried out multidisciplinary observations in the vicinity of Syowa Station and Mizuho Station between February 1982 and January 1983. The routine and fundamental observations comprising studies of aurora, geomagnetism, ionosphere, meteorology, oceanography, seismology and geodesy were performed as in the preceding years. Researches on the physical and chemical properties of the middle atmosphere and ecological investigations of marine coastal ecosystems were conducted in the Syowa Station area through the wintering season. To clarify dynamics of the ice sheet, glaciological studies were carried out in the Mizuho Plateau by the oversnow traverses, in particular the spring-summer traverse. Geological survey and meteorite search were also made in the Yamato Mountains area on the way of the spring-summer traverse.